2022
DOI: 10.1653/024.105.0210
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Parasitoid Retention on Yellow Sticky Card Traps

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Aside from Orthoptera, which are herbivores (Joern, 1979) commonly captured on these traps, we selected these taxa because they are important beneficial insects either providing biocontrol (Chalcidoidea, Ichneumonoidea, Syrphidae) or pollination services (Lepidoptera, Syrphidae) (Bonet, 2009; Herrmann et al, 2023; Skevington et al, 2019). Given that these taxa are very commonly captured and known to be sensitive to environmental conditions (Benthall et al, 2022; Eckberg et al, 2015; Holthouse et al, 2021; Toennisson et al, 2019), they provided an additional, more sensitive test beyond that which would be provided by simply examining the core taxa monitored at the site. Indeed, capture rates of four of the five additional taxa revealed a statistical difference between card types: the new cards appeared to be more attractive to Chalcid wasps, hoverflies, and Orthoptera, but less attractive to Ichneumon wasps.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from Orthoptera, which are herbivores (Joern, 1979) commonly captured on these traps, we selected these taxa because they are important beneficial insects either providing biocontrol (Chalcidoidea, Ichneumonoidea, Syrphidae) or pollination services (Lepidoptera, Syrphidae) (Bonet, 2009; Herrmann et al, 2023; Skevington et al, 2019). Given that these taxa are very commonly captured and known to be sensitive to environmental conditions (Benthall et al, 2022; Eckberg et al, 2015; Holthouse et al, 2021; Toennisson et al, 2019), they provided an additional, more sensitive test beyond that which would be provided by simply examining the core taxa monitored at the site. Indeed, capture rates of four of the five additional taxa revealed a statistical difference between card types: the new cards appeared to be more attractive to Chalcid wasps, hoverflies, and Orthoptera, but less attractive to Ichneumon wasps.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with the effects of T. japonicus population density, distribution, and host searching on its captures, detections are also likely influenced by the strength of its behavioral response to YSC and the distance over which this response occurs. Benthall et al (2022) reported that some portion of the T. japonicus captured in the type of YSC used for this project may escape by walking from the sticky surface, thus potentially under-representing captures. However, given that our use of YSC has reflected its seasonal phenology and habitat effects (Quinn et al 2021, Dyer 2022), its increasing abundance and distribution in Frederick County, and its spread in recent years, the sensitivity, practicality, and utility of this sampling tool for the purposes described here seem adequate.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from Orthoptera, which are herbivores (Joern 1979) commonly captured on these traps, we selected these taxa because they are important beneficial insects either providing biocontrol (Chalcidoidea, Ichneumonoidea, Syrphidae) or pollination services (Lepidoptera, Syrphidae) (Bonet 2009;Herrmann, Buchholz, and Theodorou 2023;Skevington et al 2019). Given that these taxa are very commonly captured and known to be sensitive to environmental conditions (Benthall et al 2022;Eckberg et al 2015;Holthouse, Spears, and Alston 2021;Toennisson, Klein, and Burrack 2019), they provided an additional, more sensitive test beyond that which would be provided by simply examining the core taxa monitored at the site. Indeed, capture rates of four of the five additional taxa revealed a statistical difference between card types: the new cards appeared to be more attractive to Chalcid wasps, hoverflies, and Orthoptera, but less attractive to Ichneumon wasps.…”
Section: Discussionmentioning
confidence: 99%